2005
DOI: 10.1038/sj.emboj.7600801
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 is a calcium-sensor for NMDA-induced AMPA receptor trafficking

Abstract: Regulation of AMPA receptor (AMPAR) trafficking results in changes in receptor number at the postsynaptic membrane, and hence modifications in synaptic strength, which are proposed to underlie learning and memory. NMDA receptor-mediated postsynaptic Ca2+ influx enhances AMPAR internalisation, but the molecular mechanisms that trigger such trafficking are not well understood. We investigated whether AMPAR-associated protein–protein interactions known to regulate receptor surface expression may be directly regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
186
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(197 citation statements)
references
References 46 publications
(77 reference statements)
11
186
0
Order By: Relevance
“…It is possible that positive AMPAR modulators could activate NMDAR as there is a link of these two receptors (Hanley and Henley, 2005) and lead to improved behavior in mGluR5 À/À animals. Indeed, we observed that both positive AMPAR modulatorsFaniracetam and CX546Fhad positive effects on impaired PPI of mGluR5 mutant mice but with different efficacies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that positive AMPAR modulators could activate NMDAR as there is a link of these two receptors (Hanley and Henley, 2005) and lead to improved behavior in mGluR5 À/À animals. Indeed, we observed that both positive AMPAR modulatorsFaniracetam and CX546Fhad positive effects on impaired PPI of mGluR5 mutant mice but with different efficacies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, using electrophysiological measurements, we found that CA1 neurons from mGluR5 À/À mice showed a complete loss of the NMDARmediated component of long-term potentiation (LTP NMDA ), but an unchanged LTP of AMPAR-mediated component (LTP AMPA ) (Jia et al, 1998). We hypothesized here that membrane depolarization via AMPAR facilitation could activate NMDAR complex as there is a link between these two receptors (Hanley and Henley, 2005) and overcome behavioral deficits of mGluR5 À/À animals. AMPAR are heteromeric complexes composed of four subunits (GluR1, GluR2, GluR3, and GluR4), each of which has a binding pocket for the transmitter glutamate and can be expressed as flip or flop splice variant, which is regulated regionally (Black, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a peripheral protein, PICK1 has been reported to interact with a series of membrane proteins including α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) [13][14][15][16], acid-sensing ion channel (ASICs) [17] and ErbB2/Her-2 [18]. In most of the cases, PICK1 acts as a critical regulator of membrane receptors' subcellular trafficking to modulate neural processes such as learning and memory [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…At the postsynaptic site, both PICK1 and NSF contribute to regulating GluA2 insertion and retraction from the plasma membrane in a calcium dependent manner (Hanley and Henley, 2005). Our data suggest that PICK1 and NSF may play a similar role in the presynaptic terminal, where overexpression of PICK1, as well as expression of pep2m, reduces the labeling intensity of GluA2 at plasma membrane and cytoplasmic sites.…”
Section: Discussionmentioning
confidence: 52%
“…The interaction between PICK1 and GluA2 is involved in the removal of GluA2 from the plasma membrane during long-term depression (LTD) in the hippocampus (Iwakura et al, 2001;Kim et al, 2001;Hanley and Henley, 2005) and the cerebellum (Xia et al, 2000;Steinberg et al, 2006;Hanley, 2008;Terashima et al, 2008).…”
Section: Introductionmentioning
confidence: 99%